Internalisasi Nilai-Nilai Moderasi Beragama Melalui Tindak Tutur Direktif Dalam Dhammadesana - Purnomo, Danang Try (Universitas Islam Negeri Raden Intan Lampung, 2021)
Religious preaching is an important part in realizing the practice of religious moderation delivered by the preacher through his actions. This is done as a form of resistance to the potential for horizontal conflicts of religious people such as acts of intolerance, hate speech, and physical conflict that can threaten religious harmony and national unity. This paper discusses the realization of a directive that reflects the moderate solicitation of religion. This type of research is descriptive-qualitative with the approach used is pragmatic, i.e. an approach that sees linguistic events based on the social context. The results showed that the correctness of the directive in the sermon represented the function of influencing his people to do something. Meanwhile, the internaslization of religious moderation values contained in religious preaching is conceptualized in three aspects, namely maintaining diversity, getting to know each other, and applying the principles of social justice.